Self Efficacy On Self Care In Coronary Heart Patients - Koto, Yeni; Solehudin, Solehudin; Kurniawan, Muhamad Okeu (International Journal of Health Sciences, 2024)
Non-communicable diseases are the leading cause of death in the world, one of the non-communicable diseases is coronary heart disease. Self-efficancy in people with heart disease is defined as confidence in the patient's ability to perform physical activity that can be affected by symptoms or complications of cardiovascular disease. Rehospitalization is not only due to the progression of the disease, but can also be caused by indifference to medication and poor self-care. Self-care is the process of maintaining health through practices that promote health, and manage diseases and symptoms. The study aims to improve the relationship between self-efficiency and self-care in coronary heart patients. The research method used in this study includes quantitative research with a sectional coss study design using a chi-square test with a sample of 70 patients suffering from coronary heart disease in the Hospital Cinere Diagram. Based on the results of the chi-square test that has been carried out obtain a p value of 0.007 or & < 0.05 where this indicates that there is a relationship between self-efficiency and self-care. The conclusion is that self-efficancy has a significant relationship with self-care in patients with coronary heart in Hospital Diagram Cinere